Analisis Strategi Bauran Promosi Paket Meeting di Hotel Syamsiah Padang Lawas (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research is motivated by the problems found by researchers related to the promotion mix at Syamsiah Padang Lawas Hotel. This study aims to determine the promotion mix strategy carried out at Syamsiah Hotel Padang Lawas. The research method used is qualitative with descriptive methods. This research was conducted at Syamsiah Hotel Padang Lawas in June-July 2020. Determination of research informants using purposive sampling technique with a total of 4 informants. The data used are primary data in the form of direct communication with informants carried out by observation, interviews, documentation and secondary data obtained from Syamsiah Hotel Management documents. Data validity checking technique is done by tringulation. The data analysis techniques used are inductive analysis, deductive analysis and SWOT analysis. Based on the results of research on the meeting package promotion mix strategy at Syamsiah Padang Lawas Hotel, it can be concluded that the hotel has strengths in utilizing various advertising media, sales promotion, personal selling, public relations, and direct marketing. Advertising strategies through social media and print media allow hotels to reach a wide market segment, while providing discounts in sales promotions can increase bookings. Personal selling is effective in building direct relationships with customers, and involvement in public relations can improve the hotel's image. Direct marketing through WhatsApp has also proven to be efficient in targeting specific customers. However, there are some weaknesses, such as the design of pamphlets and brochures that are not updated, customer dependence on discounts, limited reach of sales calls, and lack of collaboration with the media and website development. Threats from competitors, negative public perception, and strategic mistakes also need to be well anticipated. By maximizing strengths and opportunities and overcoming weaknesses and threats, Hotel Syamsiah can optimize promotional strategies to achieve better results.